The Use of English Song for Teaching Vocabulary to Young Learners - Khoirunnisa, Gita Ramadania; Rizqiya, Rissa San (PROJECT (Professional Journal of English Education), 2025)
This study focused on using the song as a teaching tool in teaching English to young students at TKA Al-Hidayah, with students aged 5-6 years old. This study aims to observe song as a teaching tool to memorize vocabulary in English. Observations and interviews were used to collect data. The research method uses descriptive qualitative. Researchers chose 10 students as participants. The results are that song lyrics can be an alternative media that teachers can use to convey teaching materials and children's interests so that children can be interested in learning English.